A Quantitative Molecular Orbital Perspective of the Chalcogen Bond - de Azevedo Santos, Lucas; van der Lubbe, Stephanie C C; Hamlin, Trevor A; Ramalho, Teodorico C; Matthias Bickelhaupt, F (ChemistryOpen, 2021)
We have quantum chemically analyzed the structure and stability of archetypal chalcogen-bonded model complexes D2 Ch⋅⋅⋅A- (Ch = O, S, Se, Te; D, A = F, Cl, Br) using relativistic density functional theory at ZORA-M06/QZ4P. Our purpose is twofold: (i) to compute accurate trends in chalcogen-bond strength based on a set of consistent data; and (ii) to rationalize these trends in terms of detailed analyses of the bonding mechanism based on quantitative Kohn-Sham molecular orbital (KS-MO) theory in combination with a canonical energy decomposition analysis (EDA). At odds with the commonly accepted view of chalcogen bonding as a predominantly electrostatic phenomenon, we find that chalcogen bonds, just as hydrogen and halogen bonds, have a significant covalent character stemming from strong HOMO-LUMO interactions. Besides providing significantly to the bond strength, these orbital interactions are also manifested by the structural distortions they induce as well as the associated charge transfer from A- to D2 Ch.
Keywords: chalcogen bonding; activation strain model; noncovalent interactions; energy decomposition analysis; density functional calculations